2013
DOI: 10.1080/10714413.2013.825514
|View full text |Cite
|
Sign up to set email alerts
|

Student, Teacher, and Administrator Perspectives on Harm: Implications for Implementing Safe and Caring School Initiatives

Abstract: Abstract:This article reports on a study that examines student, teacher and administrator perspectives on harm and how their schools address harm. It presents an overview of these perspectives within and across 3 different school environments. In doing so, the study contributes to a better understanding of the often ineffective implementation of safe and caring school initiatives. By drawing on restorative justice and relational theory, the findings illustrate how a focus on well-being and relationship is crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The study is the starting point of a broader project on the implemention of training in restorative practices in education establishments in the Balearic Islands and its impact in the life of students and staff. The growing body of research regarding the effectiveness of restorative practices (Gray & Drewery, 2011;MCluskey et ál, 2008;Reimer, 2011;Vaandering, 2013), among others; is evidence of their progressive implementation and of the need to analyse their implementation.…”
Section: Group Cohesion Is Fundamental To Preventing Conflicts (Trainmentioning
confidence: 99%
See 2 more Smart Citations
“…The study is the starting point of a broader project on the implemention of training in restorative practices in education establishments in the Balearic Islands and its impact in the life of students and staff. The growing body of research regarding the effectiveness of restorative practices (Gray & Drewery, 2011;MCluskey et ál, 2008;Reimer, 2011;Vaandering, 2013), among others; is evidence of their progressive implementation and of the need to analyse their implementation.…”
Section: Group Cohesion Is Fundamental To Preventing Conflicts (Trainmentioning
confidence: 99%
“…Restorative practices generate community by providing effective, direct ways of teaching pupils -like all adults (Morrison, 2006;Morrison et ál., 2005;Vaandering, 2013;Vaandering, 2014)that they are part of it, that their actions affect others and that they share the responsibility of making their community a place where they would like to live. Thus, restorative practices are directly related to the aim of contributing to the construction of a more democratic society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A philosophy of restorative practices emphasizes that relationships are integral to fulfilling student needs (Vaandering, 2013(Vaandering, , 2014a. Restorative practices is often referred to as restorative justice.…”
mentioning
confidence: 99%
“…However, it is still likely that principals are responding to a number of conflicting pressures and factors in addition to their own values. For example, principals are beholden to internal and external stakeholders' expectations for what a safe and orderly school environment looks like, and Vaandering (2014) has found that these expectations hold cultural sway even in a school ostensibly committed to non-punitive discipline. Zero tolerance policies created a "culture of control" (Nolan, 2006) in schools by shifting administrator mentality from educative to punitive.…”
mentioning
confidence: 99%